2012
DOI: 10.1111/jop.12006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gustatory function in HIV‐infected subjects with and without HAART

Abstract: The results document significant taste losses in HIV-infected subjects, and HAART contributes considerably to such taste perversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
4
15
2
Order By: Relevance
“…Antiretroviral drugs penetrate into the central nervous system and, therefore, may impact olfactory functions. Several studies have reported disruptive effects of HAART on olfaction and gustation (Fasunla et al 2016;Raja et al 2013). The participants of the current study, however, may be characterized with increased olfactory sensitivity.…”
Section: Limitations and Future Directionscontrasting
confidence: 45%
“…Antiretroviral drugs penetrate into the central nervous system and, therefore, may impact olfactory functions. Several studies have reported disruptive effects of HAART on olfaction and gustation (Fasunla et al 2016;Raja et al 2013). The participants of the current study, however, may be characterized with increased olfactory sensitivity.…”
Section: Limitations and Future Directionscontrasting
confidence: 45%
“…[9] Sour and bitter tastes were more affected as compared to sweet and salty tastes, which was in accordance with Raja et al . [7] The significant alteration in sour and bitter taste could be the result of adaptation to these tastes caused by continuous stimulation by HAART and also may have resulted in the higher detection threshold to it.…”
Section: Discussionmentioning
confidence: 99%
“…[56] It has also been reported that HAART therapy affects the chemosensory system in 70% of individuals and 23% of patients reported a change in the taste sensation. [7]…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral medications have been associated with dysgeusia in human immunodeficiency virus patients. 13 Chemotherapeutic drugs used for treatment of cancers, especially 5-fluorouracil and its oral analogs, have also been associated with dysgeusias, with greater prevalence in the elderly. 14 Numerous other commonly prescribed drugs, described in Table 2, can contribute to dysgeusia.…”
Section: Clinical Significancementioning
confidence: 99%